A systematic review of the relationship between motivational constructs and self-regulated learning - Sook Ling Lim; Kee Jiar Yeo (International Journal of Evaluation and Research in Education (IJERE), 2021)
The aim of this review was to identify the motivational constructs which were mostly associated with self-regulated learning and how these motivational constructs were related to self-regulated learning. There were 20 studies (N=8,759) met inclusion criteria for this review. In overall, the evidence of the included studies showed that motivational constructs such as self-efficacy, intrinsic goal orientation, task value, and control of learning beliefs were positively and significantly related to and in predicting self-regulated learning; test anxiety was negatively and insignificantly related to and in predicting self-regulated learning; inconsistent results were observed for extrinsic goal orientation as it could be positively or negatively related to and in predicting self-regulated learning.